Integration of antenatal care services with health programmes in low- and middle- income countries: systematic review - Thyra E de Jongh; Ipek Gurol-Urganci; Elizabeth Allen; Nina Jiayue Zhu; Rifat Atun (Edinburgh University Global Health Society, 2016)
Antenatal care (ANC) presents a potentially valuable platform for integrated delivery of additional health services for pregnant women-services that are vital to reduce the persistently high rates of maternal and neonatal mortality in low- and middle-income countries (LMICs). However, there is limited evidence on the impact of integrating health services with ANC to guide policy. This review assesses the impact of integration of postnatal and other health services with ANC on health services uptake and utilisation, health outcomes and user experience of care in LMICs.